Bioadaptive technology of sugar beet cultivation - Dmytryk, A. (ТДАТУ, 2018)
Therefore, with an appropriate approach to the industry, the production of sugar beets and their processing can be economically beneficial for both individual enterprises and for the state as a whole.
Keywords: industry; sugar beets; processing; soil-climatic conditions